2022
DOI: 10.3389/fbioe.2022.993436
|View full text |Cite
|
Sign up to set email alerts
|

The role of allogeneic platelet-rich plasma in patients with diabetic foot ulcer: Current perspectives and future challenges

Abstract: The frequency of chronic cutaneous wounds are sharply increasing in aging populations. Patients with age-related diseases, such as diabetes, tumors, renal failure and stroke are prone to soft tissue and skin injury, compounded by slowed healing in aging. Imbalance of wound inflammation, loss of growth factor secretion, and impairment of tissue repair abilities are all possible reasons for failed healing. Therefore, it is vital to explore novel approaches to accelerate wound healing. Platelet-rich plasma (PRP) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 77 publications
2
9
0
Order By: Relevance
“…The benefit of allogeneic PRP is that it can be collected from voluntary blood donors, and be ready to use at any time without having to collect any samples from the patient. 17,29 Moreover, it has been demonstrated that the potential immunogenicity of allogeneic PRP is not a significant risk. 30 There is a non-systematic review that discusses allogeneic PRP for wound treatment, 17 including 3 case series and 5 randomized controlled trials.…”
Section: Discussionmentioning
confidence: 99%
“…The benefit of allogeneic PRP is that it can be collected from voluntary blood donors, and be ready to use at any time without having to collect any samples from the patient. 17,29 Moreover, it has been demonstrated that the potential immunogenicity of allogeneic PRP is not a significant risk. 30 There is a non-systematic review that discusses allogeneic PRP for wound treatment, 17 including 3 case series and 5 randomized controlled trials.…”
Section: Discussionmentioning
confidence: 99%
“…Platelet derivatives, including PRP and “platelet gels” used for regenerative medicine, are still typically obtained from autologous patient-specific blood fractions [ 81 , 82 ]. However, there is now an increasing focus on considering allogeneic (donor-derived whole blood or apheresis) PCs prepared by blood establishments and hospital blood banks as starting materials to make platelet-derived biomaterials [ 17 19 , 24 27 , 83 86 ]. Preparation procedures of PCs from allogeneic blood donors by blood establishments (a term equivalent to blood centers) using whole-blood donations or plateletpheresis procedures were described in previous publications [ 9 , 10 , 87 89 ] and are summarized below.…”
Section: Allogeneic Pc Collection and Propertiesmentioning
confidence: 99%
“…Several reasons contribute to the growing interest in platelet biomaterials made from allogeneic donations rather than autologous sources. First, certain patients may face challenges in donating 50–100 mL of their own blood due to various health conditions, lack of venous access, the presence of comorbidities such as thrombocytopenia (a low platelet count), platelet dysfunctions, diabetes, peripheral arterial and neuropathic disease [ 17 19 ], or the use of antithrombotic medications, which can impact the blood-clotting process and platelet functions [ 20 ]. Secondly, the variability in autologous platelet derivatives, affecting growth factor content and immune cell and inflammatory cytokine profile, further complicates their use [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings also inspire research on biomaterials and tissue engineering since promoting dECM exposure can be a novel target. Platelet-rich plasma is a widely used biologic that is rich in TGF-β, IGF1, platelet-derived growth factor (PDGF), and other growth factors [ 108 , 121 ]. In one study, the combination of a tricalcium phosphate (TCP) material and platelet-rich plasma showed a promising therapeutic effect in the treatment of AP lesions [ 108 ].…”
Section: Msc-based Treatment For Apical Periodontitismentioning
confidence: 99%